Design for pharmacotherapeutic follow-up of psychiatric patients served in a public outpatient outpatient: Implementation study (Revista Contexto & Saúde, 2024)
Objective . Report the experience of implementing a pharmacotherapeutic monitoring service in a public outpatient psychiatric clinic. Methods . This is an implementation study using the design thinking model, developed in the mapping, creation and implementation stages, adapted from Stickdorn and Schneider. Results . Patient needs were mapped and implementation limitations were assessed. Needs for review of drug therapy, more frequent consultations, symptom monitoring and control were identified. In the creation phase, the practice model was conceptualized and structured, including anthropometric assessment, screening for symptoms of anxiety and depression, and the integration of telemonitoring services. During implementation, the model was tested with 20 patients, resulting in 114 consultations, 67.5% of which were carried out remotely and 32.5% in person. Patients were screened for hypertension (25%), diabetes (10%), depression (70%), and anxiety (60%). A total of 176 problems related to pharmacotherapy (PRF) and 612 pharmaceutical interventions (PI) were identified, with health advice (43.5%) and monitoring recommendations (19.1%) being the most frequent. Medical acceptance for therapy adjustments occurred in 41% of cases, and the absenteeism rate was 38.4%. Conclusion . Despite implementation challenges, service design proved to be relevant for configuring and standardizing the structuring process, and pharmacotherapeutic monitoring proved to be important for integrating patient care in public health environments.
Keywords: Pharmaceutical Care; Mental Health; User-Centered Design; Unified Health System